2007
DOI: 10.1021/la063344x
|View full text |Cite
|
Sign up to set email alerts
|

Manipulating the Self-Assembling Process to Obtain Control over the Morphologies of Copper Oxide in Hydrothermal Synthesis and Creating Pores in the Oxide Architecture

Abstract: Copper oxide with various morphologies was synthesized by the hydrolysis of Cu(ac)2 with urea under mild hydrothermal conditions. In the synthesis, a series of organic amines with one or two amine groups (monoamine and diamine), including isobutylamine, octylamine (OLA), dodecylamine, octadecylamine (monoamines), ethylenediamine dihydrochloride, and hexamethylenediamine (diamines), was used as the "structure-directing agent". The monoamines led to the formation of one-dimensional (1D) aggregates of the copper … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
22
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(24 citation statements)
references
References 29 publications
2
22
0
Order By: Relevance
“…The nanobundles are tightly packed together to give them a lenticular shape. A similar architecture has been observed by Zhong et al for copper oxide (Zhong et al 2007). It must be noted that increasing the hold time to 15, 30 and 60 min does not alter the product morphology: the reaction product shows only the presence of YPO 4 nanobundles (Fig.…”
Section: Mechanism Of Formationsupporting
confidence: 86%
“…The nanobundles are tightly packed together to give them a lenticular shape. A similar architecture has been observed by Zhong et al for copper oxide (Zhong et al 2007). It must be noted that increasing the hold time to 15, 30 and 60 min does not alter the product morphology: the reaction product shows only the presence of YPO 4 nanobundles (Fig.…”
Section: Mechanism Of Formationsupporting
confidence: 86%
“…Subsequently, the solution color gradually changed from black to green after 2 h (Step 3 in Scheme 1A). After incubation at 65 8C for 2 h, this green solution turned orange-yellow (Step 4 in Scheme 1A), suggesting the oxidation of Cu 2 O nanoparticles to CuO nanoparticles [31]. TEM characterization showed that the RSAs were formed during the heating process (Step 4 in Scheme 1A).…”
Section: Methodsmentioning
confidence: 99%
“…We propose that DDA plays a structure-directing role in the formation of the interconnected 1D nanowires, and rGO provides sites for anchoring Co 3 O 4 nanowires by electrostatic interaction, as illustrated in Scheme 2 [38]. In the reaction, part of the Co(DDA) n 2+ formed at the beginning of the reaction (or DDA) could anchor on the surface of GO by the electrostatic interaction between Co(DDA) n 2+ (or DDA) and the oxygencontaining groups of GO (-COOH or -OH).…”
Section: Formation Mechanism Of Co 3 O 4 -Rgo Hybridsmentioning
confidence: 99%